COMPARATIVE MORPHOMETRIC STUDY BETWEEN CONVENTIONAL AND DIGITAL IMPRESSION-TAKING - Krisztina Martha; Mariana Pacurar; Esztella Éva Kiss; Brigitta Szakacs; Izabella Éva Mureșan; Manuela Popescu (Romanian Journal of Oral Rehabilitation)
"One of the innovative inventions in dentistry is the digital scanner, which, based on the predictions, will significantly change the course of future treatments for patients, dentists and dental technicians. Objective: The aim of our study is to compare the dimensional differences between dental arches registered using the traditional and digital methods. Materials and method: We compared the digitally scanned versions of study samples (15 cases) based on alginate impressions with the intraoral scans of the same patients. The study samples were scanned with a Medit Identical Hybrid scanner, while the intraoral scans were performed with a 3Shape scanner. After all this, the impressions of each subject taken with different techniques were placed in each other using the Exocad program, and the dimensional differences were examined in different planes. Result: Our measurements are still in progress. Conclusion: Regarding our expectations, a difference between analog and digital methods is expected, as the former almost entirely depends on the person performing the experiment and its subject, while the latter can be considered more precise due to its more objective operating principle."